Smallholder livelihood resilience to climate variability in South-Eastern Kenya, 2012–2015 - Aschinger, Roman; Boillat, Sébastien; Ifejika Speranza, Chinwe (Frontiers in Sustainable Food Systems, 2023)
Climate change, land degradation, demographic change and persistent poverty pose major challenges to smallholder farmers in the arid and semi-arid lands of sub-Saharan Africa. Though many studies have focused on how resilient these households are to shocks, very few studies deal with how household resilience varies over time. We provide a longitudinal analysis to assess how the resilience of smallholder households in south-eastern Kenya has varied from 2012 to 2015. We use the Livelihood Resilience Indicator Framework to examine the linkages between livelihood outcomes and livelihood resilience (buffer capacity, self-organisation and capacity for learning). We collected data from 134 households on three resilience dimensions: buffer capacity, self-organisation, and capacity for learning. We performed principal component analysis to identify the key components of these dimensions and examine their relevance for livelihood outcomes. Our findings show that under drought conditions in 2012, conservation agriculture practices significantly contributed to maize yields. In both years 2012 and 2015, there was a positive correlation between resilience dimensions and food security. Key components of this relation were land area, income, conservation agriculture practices, climate forecasts and actions taken for the upcoming growing season.